Valorization of banana peel: a biorefinery approach - Pathak, Pranav D.; Mandavgane, Sachin A.; Kulkarni, Bhaskar D. (Reviews in Chemical Engineering, 2016)
Banana peel (BP) is an agrowaste produced in large volumes annually, especially by food-processing industries; however, its disposal is of significant concern. However, recent research suggests that BP is a valuable source of bioactive compounds, which can be converted into value-added products. This article reviews the conversion process of value-added products from BP and provides an outline on the chemical composition of BP and its possible applications. In addition, we also discuss the - utilization of BP as a substrate to produce animal feed, biofertilizer, dietary fibers, clean energy, industrial enzymes, as well as its use in the synthesis of nanomaterials. Based on the research conducted so far, it is obvious that BP has a wide variety of applications, and thus, developing a biorefinery approach to adequately utilize BP will help realize its economic benefits to the fullest. Based on the valorization of BP, a scheme for BP biorefinery has been proposed. A material balance for BP biorefinery for 1-ton bone-dry BP is presented and our results show that 432 kg of protein or 170 kg of citric acid, 170 kg of pectin, 325 m(3) of ethanol, and 220 m(3) of methane can be produced.